Optimization of the porcine liver enzymatic hydrolysis conditions. (14th January 2020) - Maluf, José U.; Fiorese, Mônica L.; Maestre, Keiti L.; Dos Passos, Fernanda R.; Finkler, Joana K.; Fleck, Jessica F.; Borba, Carlos E.
Abstract: Worldwide porcine slaughterhouses produce significant amounts of by‐products, such as porcine liver, daily. Even though the liver presents a very restricted market demand when raw, this product is composed of an exceptional nutritional content, with emphasis on protein, being, therefore, characterized as a potential raw material to produce protein hydrolysates. This article aimed to study the production of protein hydrolysate using the commercial enzymes Alcalase 2.4L™ and Novo Pro‐D™. For the development of this research, a central composite rotatable design with 4 axial points was applied for each enzyme. The factors evaluated were protein/water and enzyme/substrate ratios. The best hydrolysis results indicate average percentages of hydrolysis degree of 27.5% for both enzymes. The presence of low‐molecular‐weight peptides was also evidenced by the electrophoresis technique. It is, therefore, concluded that there is positive viability for the use of hydrolyzed porcine liver in differentiated food applications with an aggregate market value. Practical Applications: At present, the worldwide growing dissemination of food scarcity has become a stimulus for the food industry to rethink the efficient use of raw materials to avoid waste and maximize the use of existing nutritional resources. A potential way of exploiting the nutritional value of the protein by‐products with no commercial applications is their transformation into protein hydrolysates by means of enzymatic processes. Protein hydrolysates have been in focus in the scientific community with industrial applications as beneficial products to the ingesting body, for acting as either nutraceuticals or functional bioactive foods. Commercialization of this type of product has become a growing market niche. Thus, this research, which presents an investigation regarding the conditions of the porcine liver hydrolysis, fits within current issues, with innovative potential of obtainment of bioactive peptides from by‐products. Abstract : Porcine liver reuse by enzymatic hydrolysis for the production of protein hydrolyzate and its possible applications